THE CORRELATION BETWEEN READING LEGEND STORIES AND WRITING NARRATIVE TEXT AT NINTH GRADE STUDENTS OF SMPN 1 GONDANG TULUNGAGUNG IN ACADEMIC YEAR 2015/2016 - Linda Febriani; Titik Lina Widyaningsih; Agus Muharyanto (STKIP PGRI TULUNGAGUNG, 2016)
Reading legend story as a kind of narrative text can be an activity in reading.Narrative is one of important text to learn. Basically using legend story will makestudent more effective to make narrative text, whereas narrative text consists offolktale. The legend is a narrative produced and transmitted orally or in writing, abouta single, extraordinary, supernatural, or marvelous, true or fictitious, believed orslighted, often dated/localized event (experience), brought up with didactic orentertaining intent; it serves to confirm, or expand the experiential horizon of therecipient and confirm or question a momentarily valid conception of the world.Legend story is kind of narrative text. The purpose of the study is to know whether ornot there is any correlation between Reading Legend Stories and Writing NarrativeText at Ninth Grade Students.The method of this study an experimental inquiry is seen as the mostappropriate approach in determining whether co-operative learning positively affectsthe test results of the Ninth Grade Students of SMPN 1 Gondang Tulungagung.Because r counts more than r product moment tables (0.462 0,206). Based on thecalculations can be concluded that test is valid. Based on the calculations can beconcluded that test is reliable because the reliability score bigger than alpha target or0.630 0, 6. Because r counts more than r product moment tables (0 630 0,6).After all of the data were analyzed accurately based on the research, now theresearcher can draw some conclusion. The r table n= 34 with Î± = 5% is 0.462. Basedon the calculations can be concluded that test is valid. Because r counts more than rproduct moment tables (0.462 0,206).Based on the research analysis as explained above, the researcher concludedthat there is any correlation between Reading Legend Stories and Writing NarrativeText at Ninth Grade Students of SMPN 1 Gondang Tulungagung Result of thisresearch will be useful for the English students, English teachers and otherresearchers: For the Students, Based on the result the researcher hope students willable to use reading legend story to make writing narrative text more interesting whilestudent ability of reading legend stories increase writing narrative text. For theEnglish teachers. Result of this research hope can contribute to English teacher whowill be able to improve his/her English teaching method and techniques especiallyusing legend story in improve students writing ability in writing narrative text. Forthe Other reseachers.Keyword: Correlation, reading, Legend Stories, Narrative Text